Spherical symmetric cosmological model for higher dimensional space–time - Gaikwad, Varsha; Thakare, Vidya (International Multidisciplinary Research Journal, 2012)
In this paper thenecessary condition for perfect fluid distribution and the value of pressuredensity and velocity are obtained in terms of components of curvature tensor for five dimensional sphericalSymmetric space – times.